University trademarks: strategies of top Chinese universities - Yuan Liu; Tingjie Ma (Humanities & Social Sciences Communications, 2022)
Abstract Fierce, ever-increasing competition has prompted universities to pay more attention to their academic brand. Since the 1980s, top Chinese universities have begun to register trademarks and manage academic brands. After more than 20 years of hard work, what have they achieved? This paper, which conducts research based on big data on the trademarks and litigation of the 42 first-class universities, is the first systematic analysis of the trademark practices and strategies of Chinese universities. Our data show the following dimensions of top Chinese universities: the timing of the first trademark application, core trademark, non-core trademarks, trademark elements, distribution of trademarks in the Nice Classification, number of trademarks, legal status, and trademark litigation. Additionally, several typical universities, offering both positive and negative examples, were studied. Through the above analysis, we found that the application has some blind spots, there is a lack of initiative in trademark litigation, and the trademark management systems in universities are not considered relevant. To solve these problems, a range of suggestions from macro to micro is offered to help universities formulate a systematic and reasonable trademark protection strategy, strengthen the legal protection of their trademark rights, and improve their internal trademark management system.